2018
DOI: 10.1080/13102818.2017.1420427
|View full text |Cite
|
Sign up to set email alerts
|

Recent research progress in combatting root parasitic weeds

Abstract: The obligate root parasitic Orobanchaceae plants Striga, Orobanche and Phelipanche spp. parasitize economically important crops, vegetables and oil plants. They are the most devastating agricultural weed pests worldwide. Based on an analysis of the climatic requirements of these parasites, very large areas of new territory are at risk of invasion if care is not taken. Recent research in combatting root parasitic weeds was reviewed based on scientific papers reported from 2010 and onwards. The countermeasures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 198 publications
(267 reference statements)
1
28
0
Order By: Relevance
“…The tested bio-control agents were effective until 6 months, but their effect was less than that of the herbicide. These results are in agreement with those recorded by Samejima and Sugimoto (2018) who reported that the weeds can be controlled by using resistant or tolerant varieties, microbiological approach, cultural practices, chemical controls and integrated management. Boari and Vurro (2004) revealed that numerous microorganisms potentially useful for bio-controlling of Orobanche species were isolated and reported, but none had been subjected to continuous widespread use.…”
Section: Discussionsupporting
confidence: 92%
“…The tested bio-control agents were effective until 6 months, but their effect was less than that of the herbicide. These results are in agreement with those recorded by Samejima and Sugimoto (2018) who reported that the weeds can be controlled by using resistant or tolerant varieties, microbiological approach, cultural practices, chemical controls and integrated management. Boari and Vurro (2004) revealed that numerous microorganisms potentially useful for bio-controlling of Orobanche species were isolated and reported, but none had been subjected to continuous widespread use.…”
Section: Discussionsupporting
confidence: 92%
“…Successful breeding efforts have been made for many crops, such as sunflower, faba bean and pea. Both qualitative and quantitative broomrape resistance has been reported 14,15 . In sunflower, five single dominant genes ( Or1 to Or5 ) controlling resistance to races A to E of Orobanche cumana and one single dominant gene or two recessive genes controlling resistance to race F of O. cumana have been exploited 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A non-host plant could exudate germination stimulants to the soil, the broomrape would germinate but would not survive for lack of nutritional support. Thus, the non-host could be exploited in suicidal germination control strategies and commonly referred to as "trap crop" [10]. Previous studies revealed that the root exudates from switchgrass induced sunflower broomrape germination.…”
Section: Introductionmentioning
confidence: 99%